Tutela provisória da evidência: análise das hipóteses previstas no artigo 311 do código de processo civil - Frederico, Guilherme Nascimento (2024)
This work aims to analyze the institute of provisional evidence relief, notably the hypotheses addressed in Article 311 of the Code of Civil Procedure. To this end, it starts with a historical examination of the phenomenon of the constitutionalization of the process, followed by an investigation of the principles of access to justice, the effectiveness of judicial relief, and the reasonable duration of the process - all provided for in the Constitution. Subsequently, this dissertation investigates the techniques of judicial cognition, a subject related to the so-called differentiated protections. Next, it delves into the discipline of provisional relief in the Code of Civil Procedure, without neglecting the necessary inquiry into the subject as conceived by the revoked Code. The study then establishes the premise that provisional relief is a genus of which urgency relief and evidence relief are species, with the latter guiding the entire monograph. It is worth noting that the immediate realization of evident rights, regardless of the demonstration of periculum in mora, is not a novelty in the Brazilian procedural legal system. Indeed, this technique was already provided for in the 1973 Code of Civil Procedure. However, it was up to the current diploma to systematize and positivize provisional evidence relief, doing so, albeit not exhaustively, in Article 311. It is precisely the subsections of this legal provision that are examined in the research. Thus, it is affirmed that the burden of process time cannot be borne by the party that proves to have a higher chance of winning the case. Therefore, given the need to distribute the burden of process time more equitably, justly, and fairly, evidence relief aims to combat the so-called marginal damage of the process, characterized precisely by the delay inherent to the provision of judicial relief. The detailed technique allows, even without the urgency requirement, the provisional and early satisfaction of rights that appear likely based on the evidence already produced and the effective or presumed weakness of the defendant's defense